Tren Penelitian Konseling Islam: Sebuah Studi Bibliometrik - Winarni, Tri; Santosa, Hardi; Saputra, Wahyu Nanda Eka (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
This research aims to identify trends in scientific publications on Islamic counseling. The research uses bibliometric analysis involving scientific publications from 1989 to 2024 in the Scopus database. The keywords we use are "Islamic counseling" or "Islamic intervention". The analysis results show that the trend of scientific publications with these two keywords has increased significantly, with the peak occurring in 2020-2024. The United States is the country that has the highest contribution to scientific publications about Islamic counseling. Most articles on Islamic counseling are published in the Islamic Guidance and Counseling Journal. Tim Haesebrouck is a well-known researcher who has the most publications, while Hooman Keshavarzi is a researcher who has the most total citations. The results open up opportunities to conduct further research in areas that have not been widely researched, such as COVID-19, spirituality, violence, and conflict. The results of this research have implications for efforts to develop Islamic counseling science.